2015
DOI: 10.1371/journal.pone.0119198
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Homeobox Gene Family in Legumes: Identification, Gene Duplication and Expression Profiling

Abstract: Homeobox genes encode transcription factors that are known to play a major role in different aspects of plant growth and development. In the present study, we identified homeobox genes belonging to 14 different classes in five legume species, including chickpea, soybean, Medicago, Lotus and pigeonpea. The characteristic differences within homeodomain sequences among various classes of homeobox gene family were quite evident. Genome-wide expression analysis using publicly available datasets (RNA-seq and microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 71 publications
1
42
0
Order By: Relevance
“…From this investigation a total of seventeen common drought responsive genes from shoot and root were recovered. Importantly, to elucidate the role of candidate genes responding under drought stress, Bhattacharjee et al (2015) reported higher upregulatory role of Ca_19899 (homeobox gene) in shoot tissue and down-regulatory role of Ca_00550 gene both in root and shoot under drought stress. To mitigate the toxic effect of ROS activity produced under drought stress, Mahdavi Mashaki et al 2018unveiled up-regulatory activity of three genes (in Hashem) and Ca_04125 gene (in Bivanij) involved in safeguarding cells against ROS toxicity.…”
Section: Functional Genomic Resources For Drought and Heat Stress Tolmentioning
confidence: 99%
“…From this investigation a total of seventeen common drought responsive genes from shoot and root were recovered. Importantly, to elucidate the role of candidate genes responding under drought stress, Bhattacharjee et al (2015) reported higher upregulatory role of Ca_19899 (homeobox gene) in shoot tissue and down-regulatory role of Ca_00550 gene both in root and shoot under drought stress. To mitigate the toxic effect of ROS activity produced under drought stress, Mahdavi Mashaki et al 2018unveiled up-regulatory activity of three genes (in Hashem) and Ca_04125 gene (in Bivanij) involved in safeguarding cells against ROS toxicity.…”
Section: Functional Genomic Resources For Drought and Heat Stress Tolmentioning
confidence: 99%
“…NGS technologies have now been applied to many important crop plants to help understand the genetics of complex traits, and to provide insight into genomic variations, such as single nucleotide polymorphisms (SNPs), insertions/deletions, and other structural of variances (O'Rourke, Bolon, Bucciarelli, & Vance, ; Valliyodan et al, ; Yuan, Bayer, Batley, & Edwards, ). These advanced technologies have also facilitated the development of gene expression atlases and increased our understanding of the signalling pathways involved in the responses of plants to environmental stresses (Abdelrahman et al, ; Abdelrahman, Suzumura, et al, ; Abdelrahman, El‐Sayed, Sato, et al, ; Bhattacharjee, Ghangal, Garg, & Jain, ; Nasr Esfahani et al, ; Zhang, Chu, & Zhang, ). However, during domestication, the genomes of many crop species have changed relative to that of their wild progenitors, with increasing numbers of repetitive DNA sequences that can lead to incomplete or misassembled regions when NGS is used for sequencing, as NGS‐read lengths are too short to adequately cover these repeats (Abdelrahman, Suzumura, et al, ; Flint‐Garcia, ; Pavlovich, ; Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gene duplication events can serve as a key mechanism for increasing gene family diversity, particularly through nonfunctionalization, subfunctionalization, and new functionalization of duplicated genes. Subfunctions and new functional duplication lead to functional diversity within the family and can be expressed in different tissues or at different developmental stages than their progenitor cells [43]. Gene replication and diversification events are well documented in Arabidopsis [44].…”
Section: Gene Duplication and Expression Patterns Of Duplicated Aat Gmentioning
confidence: 99%